A comparative study of efficacy of gabapentin in inflammation induced neuropathic animal pain models with conventional analgesic diclofenac - Swarup, Arunim; Agarwal, Ruchika; Malhotra, Sunil; Dube, Abhay Shankar (International Journal of Research in Medical Sciences, 2016)
Background: Some antiepileptic drugs have been shown to be clinically efficacious in treatment of neuropathic pain and are being used by clinicians. This study is proposed to evaluate the efficacy of these drugs as compared to conventional analgesics. Methods: Formalin test has been used as the model of acute and chronic inflammatory pain. Formalin has been characterized by the occurrence of two characteristic phases of increased pain sensitivity in rats. The test drugs have been administered orally and scored according to a pain scale. Pain has been quantified by counting the incidence of spontaneous flinches, shakes and jerks of the formalin injected paw. Analgesic response or protection has been indicated if both paws are resting on floor with no obvious favouring of injected paw. Treatment group was compared with appropriate control groups using “student t test”. Results: Per oral administration of gabapentin produced no any marked effect on early phase response of formalin test but significantly suppressed the late phase response while diclofenac produced significant antinociceptive effect in both phases of formalin test. Conclusions: Thus we have observed that gabapentin produced antinociception in second phase of formalin test which reflects chronic inflammatory pain.